Attachment and Proliferation of Osteoblasts on Lithium-Hydroxyapatite Composites. (24th April 2012) - Shainberg, Ana Paula M.; Valério, Patrícia; Zonari, Alessandra; Oktar, Faik N.; Ozyegin, Lutfiye S.; Graça, Manuel Pedro F.; Leite, Maria F.; Goes, Alfredo M.
Abstract : The biocompatibility and bioactivity properties of hydroxyapatites (HAs) modified through lithium addition were investigated. Hydroxyapatites obtained from bovine bone were mixed with lithium carbonate (Li), in the proportions of 0.25, 0.50, 1.00, and 2.00% wt, and sintered at 900°, 1000°, 1100°, 1200°, and 1300°C, creating LiHA samples. The osteoblast culture behavior was assessed in the presence of these LiHA compositions. The cellular interactions were analyzed by evaluating the viability and cellular proliferation, ALP production and collagen secretion. The cytotoxic potential was investigated through measurement of apoptosis and necrosis induction. The process of cellular attachment in the presence of the product of dissolution of LiHA, was evaluated trough fluorescence analysis. The physical characteristics of these materials and their cellular interactions were examined with SEM and EDS. The results of this study indicate that the LiHA ceramics are biocompatible and have variable bioactivities, which can be tailored by different combinations of the concentration of lithium carbonate and the sintering temperature. Our findings suggest that LiHA 0.25% wt, sintered at 1300°C, combines the necessary physical and structural qualities with favorable biocompatibility characteristics, achieving a bioactivity that seems to be adequate for use as a bone implant material.